How do gait frequency and serum-replacement interval affect polyethylene wear in knee-wear simulator tests? - Reinders, Jörn; Sonntag, Robert; Kretzer, Jan Philippe (Journal of materials science, 2014)
Polyethylene wear (PE) is known to be a limiting factor in total joint replacements. However, a standardized wear test (e.g. ISO standard) can only replicate the complex in vivo loading condition in a simplified form. In this study, two different parameters were analyzed: (a) Bovine serum, as a substitute for synovial fluid, is typically replaced every 500,000 cycles. However, a continuous regeneration takes place in vivo. How does serum-replacement interval affect the wear rate of total knee replacements? (b) Patients with an artificial joint show reduced gait frequencies compared to standardized testing. What is the influence of a reduced frequency? Three knee wear tests were run: (a) reference test (ISO), (b) testing with a shortened lubricant replacement interval, (c) testing with reduced frequency. The wear behavior was determined based on gravimetric measurements and wear particle analysis. The results showed that the reduced test frequency only had a small effect on wear behavior. Testing with 1 Hz frequency is therefore a valid method for wear testing. However, testing with a shortened replacement interval nearly doubled the wear rate. Wear particle analysis revealed only small differences in wear particle size between the different tests. Wear particles were not linearly released within one replacement interval. The ISO standard should be revised to address the marked effects of lubricant replacement interval on wear rate.
Gesehen am 18.12.2020